Redox Noninnocent Monoatomic Silicon(0) Complex ("Silylone"): Its One-Electron-Reduction Induces an Intramolecular One-Electron-Oxidation of Silicon(0) to Silicon(I) - Yao, Shenglai; Kostenko, Arseni; Xiong, Yun; Ruzicka, Ales; Driess, Matthias (Journal of the American Chemical Society, 2020)
A monatomic zerovalent silicon(0) complex ("silylone") stabilized by the chelating bis(silylenyl)-ortho-carborane ligand, 1,2-(LSi)2-1,2-C2B10H10 [L = PhC(NtBu)2], has been synthesized from the redox reaction of the dipotassium bis(silylenyl)-nido-carboranate salt, 1,2-(LSi)2-1,2-C2B10H10K2, and NHC-SiCl2 (NHC = {[HCN(2,6-iPr2C6H3)]2C:}). Markedly different from previous examples, this silylone undergoes reduction due to the closo-C2B10 cluster backbone, which is prone to accept up to two electrons to form the cage-opened dianionic nido-C2B10 cluster core. Surprisingly, the closo-C2B10 core of the silylone consumes only one molar equiv of potassium naphthalenide, in addition, one electron is intramolecularly transferred from the Si0 atom to the C2B10 core to form an elusive bis(silylene)-stabilized SiI radical cation which undergoes homocoupling to the corresponding isolable dicationic SiI-SiI complex.